1989
DOI: 10.1063/1.857476
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of helical decaying turbulence

Abstract: The dynamics of helical decaying homogeneous turbulence is investigated in direct numerical simulations at moderate Reynolds numbers. A new initialization procedure is presented that allows one to control both the energy and the helicity spectral density of the initial flow field. It is observed that large initial helicity impedes the transfer of energy toward smaller scales, inhibits the buildup of enstrophy, and reduces dissipation for several turnover times. Also, the skewness and flatness of the velocity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 18 publications
4
36
0
1
Order By: Relevance
“…The PDF of the helicity angle in Fig. 3 quickly changes into a distribution with peaks concentrated at cos θ = ±1 as reported in other turbulent flows [9,10]. The appearance of the in- FIG.…”
mentioning
confidence: 85%
“…The PDF of the helicity angle in Fig. 3 quickly changes into a distribution with peaks concentrated at cos θ = ±1 as reported in other turbulent flows [9,10]. The appearance of the in- FIG.…”
mentioning
confidence: 85%
“…To elaborate this statement, consider interaction (4.12) and assume that |a k | and |a p | are 0(1) and |a~| ~0 and k>p. Differentiating the last equation and substituting the first two equations for ä* k and ä p gives ä~q+ co 2 It thus appears that a spectrum of only positive and slightly decreasing helicity may be a relatively stable configuration. Recently Polifke and Shtilman [39] have performed a numerical integration of the NavierStokes equations on a (64) 3 grid. They compared strongly helical with nonhelical flow and found that large initial helicity impedes the transfer of energy towards smaller scales.…”
Section: Two Hydrodynamic Scenariosmentioning
confidence: 99%
“…However, Kraichnan and Panda [12] showed that local helicity fluctuations are not enough to explain the observed reduction of nonlinearity, but that a certain preferential alignment of the wave vector and the Lamb vector is needed to explain the observed reduction of nonlinear interaction. Even though this study showed that local helicity fluctuations might not be the sole actor in the reduction of nonlinear transfer, helicity, at least in the average sense, plays a role in it [13].…”
mentioning
confidence: 99%